CITA HUKUM PANCASILA SEBAGAI LANDASAN FILOSOFIS POLITIK HUKUM HAK KEKAYAAN INTELEKTUAL - Herlina Ratna (Universitas Bandar Lampung (UBL), 2019)
This research starts from the importance of protecting national interests in IntellectualProperty law. Amendments to the IPR Law adopted more of the principles of TRIPsAgreement than the principles of national law originating from Pancasila and the 1945Constitution. Indonesia needs an IPR legal politics that can be a guideline in renewing theIPR Law to protect national interests. The problems examined in this study are what theprinciples of IPR law derive from Pancasila, the 1945 Constitution and the social realities ofthe Indonesian nation which can be the legal basis for the regulation of Indonesian IPR. Thisstudy uses a normative juridical approach, with the method of law approach, conceptualapproach, principles of IPR law, political description of Indonesian IPR law, and IPR Lawsthat want to be formed in the future. Analysis of legal material is carried out qualitatively.The results of the study are the principles of Indonesian IPR law, consisting of the principleof freedom of work, the principle of legal protection against IPR, the principle of benefit, theprinciple of economic rights, the principle of human welfare, the principle of protectingnational culture, the principle of state authority to implement IPR for the national interestprotection with dimensions of morality and religion, the principle of limited exclusive rights,the principle of justice, the principle of social function and the principle of collectivism.Advice from the Government and Parliament must be highly committed, have political will,courage and nationalist spirit to realize the goals of the Republic of Indonesia as written inthe Opening of the fourth Alenia 1945 Constitution in forming or revising the Indonesian IPRLaw